Abrogation of graft ischemia‐reperfusion injury in ischemia‐free liver transplantation. Issue 4 (26th April 2022) - Guo, Zhiyong; Xu, Jinghong; Huang, Shanzhou; Yin, Meixian; Zhao, Qiang; Ju, Weiqiang; Wang, Dongping; Gao, Ningxin; Huang, Changjun; Yang, Lu; Chen, Maogen; Zhang, Zhiheng; et al.
Abstract: Background: Ischemia‐reperfusion injury (IRI) is considered an inherent component of organ transplantation that compromises transplant outcomes and organ availability. The ischemia‐free liver transplantation (IFLT) procedure has been developed to avoid interruption of blood supply to liver grafts. It is unknown how IFLT might change the characteristics of graft IRI. Methods: Serum and liver biopsy samples were collected from IFLT and conventional liver transplantation (CLT) recipients. Pathological, metabolomics, transcriptomics, and proteomics analyses were performed to identify the characteristic changes in graft IRI in IFLT. Results: Peak aspartate aminotransferase (539.59 ± 661.76 U/L versus 2622.28 ± 3291.57 U/L) and alanine aminotransferase (297.64 ± 549.50 U/L versus 1184.16 ± 1502.76 U/L) levels within the first 7 days and total bilirubin levels by day 7 (3.27 ± 2.82 mg/dl versus 8.33 ± 8.76 mg/dl) were lower in the IFLT versus CLT group (all p values < 0.001). The pathological characteristics of IRI were more obvious in CLT grafts. The antioxidant pentose phosphate pathway remained active throughout the procedure in IFLT grafts and was suppressed during preservation and overactivated postrevascularization in CLT grafts. Gene transcriptional reprogramming was almost absent during IFLT but was profound during CLT. Proteomics analysis showed that "metabolism of RNA" was the major differentially expressed process between the two groups. Several proinflammatory pathways were not activated post‐IFLT as they were post‐CLT. The activities of natural killer cells, macrophages, and neutrophils were lower in IFLT grafts than in CLT grafts. The serum levels of 14 cytokines were increased in CLT versus IFLT recipients. Conclusions: IFLT can largely avoid the biological consequences of graft IRI, thus has the potential to improve transplant outcome while increasing organ utilization. Abstract : Ischemia free liver transplantation (IFLT) procedure can largely avoid the biological consequences of graft ischemia‐reperfusion injury. IFLT maintains active pentose phosphate pathway (PPP) metabolism and redox homeostasis. IFLT prevents hepatocytes death and the activation of inflammation and immune response.